The influence of fundamental analysis and systematic risk towards stock price of banks in Indonesia - Purwanto Purwanto; Erynda Bhita Safira (Journal of Business Studies and Management Review, 2020)
This research aims to identify and gives the empirical proven of significant influences in partial and simultaneously of four independent variables towards the stock price. In addition, this research chooses the population in the banking industry listed on the LQ45 index during the period of 2011-2014. Through purposive sampling and pooling data, this research has got 96 observations from six companies in four years with a quarterly basis that fulfills the criteria. Based on the result, there is debt to equity ratio, earnings-per-share, and return on equity which having significant influences towards the stock price. On the other hand, systematic risk has no significant influence on the stock price. Simultaneously, those four independent variables provide 69.7% influences to the dependent variable. The rest, 30.3%, is influenced by other factors outside this research. Moreover, earnings-per-share is chosen as the most significant factor that influences stock price.